2008
DOI: 10.1086/589107
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fatty Acid Composition and the Hibernation Patterns in Free‐Ranging Arctic Ground Squirrels

Abstract: Laboratory experiments have demonstrated that the amount of polyunsaturated fatty acids (PUFAs) in the diet before hibernation influences patterns of mammalian torpor. The hibernation ability of ground squirrels is greatest (longest torpor bouts, greatest number of animals entering torpor) when the PUFA content of their fall diets is 33-74 mg/g, under laboratory conditions. The extent to which natural fall diets both (a) vary in PUFA content and (b) influence the torpor patterns of free-ranging populations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 36 publications
(51 reference statements)
0
33
0
Order By: Relevance
“…Finally, we do not have data on the fatty acid composition of foods consumed by WNS-affected bats prior to hibernation. This may be important, as previous work has shown that the level of polyunsaturated fatty acids in the diet can influence the expression of torpor in hibernating mammals (Frank, 2008). Although these constraints may limit the interpretation of our data, we argue that comparisons of WNS-affected bats to individuals outside the range of WNS may be the best method of comparison until effective methods for detecting WNS in the field are developed.…”
Section: Discussionmentioning
confidence: 91%
“…Finally, we do not have data on the fatty acid composition of foods consumed by WNS-affected bats prior to hibernation. This may be important, as previous work has shown that the level of polyunsaturated fatty acids in the diet can influence the expression of torpor in hibernating mammals (Frank, 2008). Although these constraints may limit the interpretation of our data, we argue that comparisons of WNS-affected bats to individuals outside the range of WNS may be the best method of comparison until effective methods for detecting WNS in the field are developed.…”
Section: Discussionmentioning
confidence: 91%
“…As summer progresses, ground squirrels switch from being primarily herbivores to increasing the proportion of grains in their diet. This switch corresponds with an increase in the dietary content of essential PUFA, which are incorporated into depot fats and membrane phospholipids (102,103,131). Laboratory studies show that diets supplemented with moderately high linoleic acid (18:2, n-6) result in a higher proportion of animals entering torpor, lower torpor T b and longer bout duration during hibernation or daily torpor in chipmunks (119), deer mice (114), and goldenmantled ground squirrels (101), but not 13-lined ground squirrels (120).…”
Section: Food Quantity and Qualitymentioning
confidence: 99%
“…Laboratory studies show that diets supplemented with moderately high linoleic acid (18:2, n-6) result in a higher proportion of animals entering torpor, lower torpor T b and longer bout duration during hibernation or daily torpor in chipmunks (119), deer mice (114), and goldenmantled ground squirrels (101), but not 13-lined ground squirrels (120). In the wild, a diet containing moderate PUFA levels (33-74 mg/g) improves the ability of Arctic ground squirrels to survive the hibernation season, compared with diets containing more than 74 mg/g of PUFA (103). The moderate PUFA diet also corresponds with longer torpor bouts, fewer arousals, more days spent torpid, and shorter combined durations of arousal, IBE and entrance (103).…”
Section: Food Quantity and Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several species of hibernating rodents experience longer hibernation periods, reduced arousal activity, and lower body temperatures after consuming diets high in PUFA compared with diets high in SFA (Geiser and Kenagy 1987;Geiser et al 1994;Harlow and Frank 2001;Frank et al 2008). This is thought to be due to the preferential incorporation of PUFAs into the animals' cell membranes and storage lipids where they are presumably more metabolizable at colder body temperatures than SFAs (Geiser and Kenagy 1987;Frank et al 2008). In addition to hibernation patterns, we wanted to know whether brown bears would show evidence of harmful health conditions that humans tend to develop while eating diets high in SFA and more refined foods.…”
Section: Introductionmentioning
confidence: 99%